Agnosticism Without Ontology? The Search for New Conceptual Tools to Describe the Semi-Secular Condition in Sweden - Peder Thalén (Philosophies, 2025)
This article discusses the future role of agnosticism and its possible meaning in a post-secular, Western cultural sphere, with a special focus on the situation in Sweden. A characteristic of this context, which gives agnosticism a different role than before, is a diminishing interest in traditional ontological questions such as the existence of God. This assumption is illustrated by a comparative analysis of four examples of how atheism and secular views of life are shaped today, all of which in one way or another cross the line between religious and secular but also give philosophical questions about what exists or not a diminished role. It is argued in this article that a revised concept of agnosticism, detached from ontological thinking, together with such concepts as semi-secularity, post-atheism and post-secularity, can offer conceptual instruments for a better understanding of the main tendencies in our time.